Answers

2015-09-22T16:05:58+05:30

given,
        qr ⊥ pr 
to prove,
         ∠ros=1/2(∠qos-∠pos)
PROOF:  ∠por=90 
                ⇒∠pos+∠sor=90
                ⇒∠ros=90-∠ pos---------------(1)
                ∠qor=90(∵qr⊥pr)
                ⇒∠qos-∠ros=90
                ⇒∠ros=∠qos-90--------------------(2)                                                        from (1) and(2)we get,
               ∠ros+∠ros=90-∠pos-90+∠qos
                ⇒2∠ros=∠qos-∠pos
                ⇒∠ros=1/2(∠qos-∠pos)


0